Fatal encephalopathy with wild‐type JC virus and ruxolitinib therapy. Issue 6 (16th October 2019) - Reoma, Lauren Bowen; Trindade, Christopher Julius; Monaco, Maria Chiara; Solis, Jamie; Montojo, Marta Garcia; Vu, Phuong; Johnson, Kory; Beck, Erin; Nair, Govind; Khan, Omar I.; Quezado, Marta; Hewitt, Stephen M.; et al.
Abstract : Objective: JC virus (JCV) infection is a lytic infection of oligodendrocytes in progressive multifocal leukoencephalopathy; less common forms of central nervous system manifestations associated with JCV infection include granule cell neuronopathy, encephalopathy, and meningitis. Presented is the first case of fatal JCV encephalopathy after immunosuppressive therapy that included ruxolitinib. Methods: Postmortem analysis included next generation sequencing, Sanger sequencing, tissue immunohistochemistry, and formalin‐fixed hemisphere 7T magnetic resonance imaging. Results: JCV DNA isolated from postmortem tissue samples identified a novel 12bp insertion that altered the transcription site binding pattern in an otherwise "wild‐type virus, " which has long been thought to be the nonpathogenic form of JCV. Anti‐VP1 staining demonstrated infection in cortical neurons, hippocampal neurons, and glial and endothelial cells. Interpretation: This expands the spectrum of identified JCV diseases associated with broad‐spectrum immunosuppression, including JAK‐STAT inhibitors, and sheds light on an additional neurotropic virus strain of the archetype variety. ANN NEUROL 2019;86:878–884